Morphological characterization, pathogenicity screening, and molecular identification of Fusarium spp. isolates causing post-flowering stalk rot in maize - Harish, J.; Jambhulkar, Prashant P.; Bajpai, Ruchira; Arya, Meenakshi; Babele, Piyoosh K.; Chaturvedi, Sushil K.; Kumar, Anil; Lakshman, Dilip K. (Frontiers in Microbiology, 2023)
Post flowering stalk rot (PFSR) of maize caused by the Fusarium species complex is a serious threat to maize production worldwide. The identification of Fusarium species causing PFSR based on morphology traditionally relies on a small set of phenomic characteristics with only minor morphological variations among distinct Fusarium species. Seventy-one isolates were collected from 40 sites in five agro-climatic zones of India to assess the diversity of Fusarium spp. associated with maize crops showing symptoms of PFSR in the field. To investigate the pathogenicity of Fusarium spp. causing PFSR sixty isolates were toothpick inoculated between the first and second node at 55 days after sowing during the tassel formation stage of the crop in Kharif (Rainy season), and Rabi (Winter season) season field trials. Ten most virulent Fusarium isolates, based on the highest observed disease index, were identified by homology and phylogenetic analyses of partial sequences of the translation elongation factor 1 α (Tef-1α). Based on morphological traits such as mycelial growth patterns and mycelial pigmentation, Fusarium isolates were divided into nine clusters. The isolates were judged to be virulent based on their ability to decrease seedling vigour in in-vivo situations and high disease severity in field experiments. Pathogenicity test during the Kharif season showed 12 isolates with virulent disease symptoms with a mean severity ranging between 50 to 67 percent disease index (PDI) whereas in Rabi season, only five isolates were considered virulent, and the mean severity ranged between 52 to 67 PDI. Based on pathological characterization and molecular identification, 10 strains of Fusarium species namely, Fusarium acutatum (2/10), Fusarium verticillioides (Syn. Gibberella fujikuroi var. moniliformis) (7/10), Fusarium andiyazi (2/10) recorded the highest diseases index. All these species are part of the Fusarium fujikuroi species complex (FFSC). The distribution of virulent isolates is specific to a geographical location with a hot humid climate. Increased knowledge regarding the variability of Fusarium spp. responsible for PFSR of maize occurring across wide geographical locations of India will enable more informed decisions to be made to support the management of the disease, including screening for resistance in maize-inbred lines.